The association between food addiction, eating attitudes, self-esteem, and emotional appetite: a cross-sectional study - Sanlier, Nevin; Alyakut, Omur (Frontiers in Psychology, 2025)
BackgroundEating behavior is a multidimensional construct shaped by physical, emotional, and psychological factors. This study investigated the relationships and effects of self-esteem, emotional appetite, and food addiction on eating attitudes among young adults, while also assessing the role of demographic variables in relation to eating attitudes (EAT-26 scores).MethodsData were collected from 766 participants (171 women, 595 men) using the Eating Attitudes Test-26 (EAT-26), Rosenberg Self-Esteem Scale (RSB), Emotional Appetite Questionnaire (EMAQ), and Yale Food Addiction Scale (YFAS).ResultsAmong the participants, 71.7% had a healthy weight, 13.0% were underweight, and 15.2% were overweight or obese. Significant associations were observed between the EAT-26 eating preoccupation subscale and educational level, smoking, skipping snacks, eating out (p < 0.05), and body mass index (BMI) (p < 0.01). The restriction subscale was positively correlated with BMI and perceived adequate nutrition (p < 0.01), whereas the social pressure subscale was negatively correlated with educational status, BMI (p < 0.01), and skipping snacks (p < 0.05). The EAT-26 total score was significantly associated with self-esteem (RSB), negative emotional appetite (EMAQ negative), and food addiction (YFAS) (p < 0.01). Further analyses identified gender (B = −2.00; p < 0.05), negative emotional appetite (B = 0.03; p < 0.05), and food addiction (B = 0.496; p < 0.01) as significant predictors of EAT-26.ConclusionThe results indicate that eating behavior is most strongly influenced by food addiction, negative emotional appetite, and low self-esteem, underscoring the decisive role of psychological factors.